The role of taxes in financing the state budget for years(2013-2015) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The purpose of this research is to identify the most important features of the Iraqi tax system, the volume of tax revenues and its role in financing the state budget to cover the public expenditure for the years 2013-2015. This research is particularly important for its implications for future development in Iraq through public revenues and public expenditure. The importance of research is reflected in the endeavor to develop one of the sources of financing the general budget of the state, which is direct and indirect taxes for the revenues it provides to enable the state to play the role that commensurate with the capacity of the taxpayers.And the problem of examining the role of taxes in financing the state budget. The study assumes that the nature of taxes imposed affect the state budget. The researchers used a series of previous studies, books, and other sources related to theresearch subject. This was done through the framework of the maturity and the practicalaspect of the financial statements . The main conclusions reached were:1- The role of direct taxes in providing the general budget of a state with revenues compared to the total income, was clear in certain years2- The importance of indirect taxes increased significantly during the introduction of new taxes and raise the prices of certain fees, which contributed to the financing of the state budget.The most important recommendations reached were:1-Direct taxes have been reduced as a result of the reliance on certain taxes and the failure to develop new methods commensurate with what is appropriate to other countries, recommending the use of methods that are compatible with the development of directtaxes.2-The researchers recommend the development of other types of indirect taxes because of their role in financing the state budget revenues needed to cover the expenses in a manner appropriate to the economic situation of the country.